Greenback-gold returns and expectations of resumption, 1862 - 1879 - Gregor W. Smith; R. Todd Smith (Queen's University, Department of Economics, 1996)
We propose a unified framework for studying the greenback-gold price during the U.S. suspension of convertibility from 1862 to 1879. The gold price is viewed as a floating exchange rate, with a fixed destination given by gold standard parity because of the prospect of resumption. We test this perspective using daily data for the entire period, and measure the effect of news during and after the Civil War. New evidence of a decline in the volatility of gold returns after the Resumption Act of 1875 provides statistical support for the importance of expectations of resumption.
Keywords: N21; 330; greenbacks; gold standard; regime switching